Critical health-disease transition in the family: Nursing intervention in the lived experience - Anabela Pereira Mendes
ABSTRACT Objective: To analyse the strategies found by families to deal with the situation of critical illness, in their lived experience in a family and in an inpatient context. Method: This research fits into a qualitative paradigm and a phenomenological approach, according to Van-Manen. Participants were referred to a "snowball" effect method and the data was collected through interviews with open-ended questions. Results: From the collected data three essential themes emerged revealing the strategies: Being aware; Building dialogue; Ensuring comfort. Final considerations: In the therapeutic intervention nurses verify that families facing a critical-illness interact between themselves and with the ICU team. Families interacting with nurses can find cognitive and emotional support allowing them to be aware of the situation and to speak about it in order to strengthen and to comfort themselves.